The Moderation of Gender and Level of Vividness in The Effect of Content Types on Consumer Engagement - Wijaya, Tony (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study examines the influences of rational and emotional content on Instagram consumer engagement moderated by gender and the level of media vividness. This research is a survey. This study uses primary data collected with a scale of consumer involvement and content type. The population in this study are consumers who are Instagram users. The sampling technique used was purposive sampling with the criteria of users involved in posting activities on Instagram and following Instagram ad posts. The sample that was collected was 709 respondents from the Special Region of Yogyakarta and Central Java. The data analysis technique used moderated regression analysis (MRA). The results showed that the type of content affected on consumer engagement. The results show that female consumers reinforce emotional content rather than rational, and vice versa for male consumers. The results also show the interaction of vividness level with marketing content types. The high vividness strengthens the influence of emotional content compared to rational content, and vice versa in the low vividness. Keywords: marketing content, digital marketing, social media, instagram, e-business